Provision Of Local Food-Based Supplementary Feeding For Undernourished Toddlers In Primary Care: A Systematic Literature Review - Asyifa Tsulus Sandi; Titik Kuntari; Utami Utami; Raden Edi Fitriyanto; Yaltafit Abror Jeem; Yayuk Fathonah; Tien Budi Febriani; Emi Azmi Choironi; Gita Yusmira; Rini Syahriani; Mohamad Rahman Suhendri (CV. AFDIFAL MAJU BERKAH, 2026)
Undernutrition among children under five in Indonesia remains aggravated by poor diet quality and comorbidities such as tuberculosis, anemia, and thalassemia. This review evaluated the effectiveness of local food-based supplementary feeding compared with standard supplements or no intervention, assessed the moderating role of major comorbidities on nutritional recovery, and identified determinants of program success. A PRISMA 2020-guided systematic literature review was conducted using Consensus.app sources published in 2015–2026, prioritizing systematic reviews, meta-analyses, randomized controlled trials, and quasi-experimental studies. Supplementary foods and complementary feeding interventions improve recovery, body weight, Weight-for-Height Z-Score (WHZ), Weight-for-Age Z-Score(WAZ), dan Mid-Upper Arm Circumference (MUAC), sementara perbaikan tinggi badan whereas gains in height/ Height-for-Age Z-Score (HAZ) are smaller and require longer exposure. Local food-based products, including moringa-fortified foods, moringa nuggets, and other locally formulated diets, also improved weight, height, or Mid-Upper Arm Circumference (MUAC) in studies from Indonesia and other low-resource settings. Tuberculosis and anemia consistently predicted slower nutritional recovery, while evidence for thalassemia mainly indicates elevated malnutrition risk rather than tested response to supplementary feeding. Program success depends on adequate duration, adherence, nutrient composition, training, family support, and primary care delivery capacity. The main research gap is the lack of integrated screening for tuberculosis, anemia, and thalassemia within primary-care supplementary feeding programs. Locally-based PMT effectively improves short-term nutritional status of undernourished children, but its effectiveness decreases in children with TB and anemia comorbidities. Integration of tuberculosis, anemia, and thalassemia screening in PMT programs at primary healthcare facilities is needed.